2010
DOI: 10.1051/0004-6361/200913780
|View full text |Cite
|
Sign up to set email alerts
|

Accretion-driven turbulence as universal process: galaxies, molecular clouds, and protostellar disks

Abstract: Context. Even though turbulent motions are found everywhere in astrophysical systems, the origin of this turbulence is poorly understood. When cosmic structures form, they grow in mass via accretion from their surrounding environment. Aims. We propose that accretion is able to drive internal turbulent motions in a wide range of astrophysical objects and study this process in the case of galaxies, molecular clouds, and protoplanetary disks. Methods. We use a combination of numerical simulations and analytical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
359
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(371 citation statements)
references
References 150 publications
10
359
2
Order By: Relevance
“…The fact that we see turbulence thus leads us to conclude that it must be driven by some physical stirring mechanism. In general, potential driving mechanisms include supernova explosions and expanding radiation fronts and shells induced by high-mass stellar feedback (McKee 1989;Balsara et al 2004;Krumholz et al 2006;Breitschwerdt et al 2009;Goldbaum et al 2011;Peters et al 2011;Lee et al 2012), winds , gravitational collapse and accretion of material (Vazquez-Semadeni et al 1998;Elmegreen & Burkert 2010;Klessen & Hennebelle 2010;Vázquez-Semadeni et al 2010;Federrath et al 2011b;Robertson & Goldreich 2012;Lee et al 2015), and Galactic spiral-arm compressions of H I clouds turning them into molecular clouds (Dobbs & Bonnell 2008;, as well as magnetorotational instability (MRI) and shear (Piontek & Ostriker 2007;Tamburro et al 2009). Jets and outflows from young stars and their accretion disks have also been suggested to drive turbulence (Norman & Silk 1980;Matzner & McKee 2000;Banerjee et al 2007;Nakamura & Li 2008;Cunningham et al 2009Cunningham et al , 2011Carroll et al 2010;Wang et al 2010;Plunkett et al 2013Plunkett et al , 2015Federrath et al 2014;Offner & Arce 2014).…”
Section: Turbulence Driving?mentioning
confidence: 99%
“…The fact that we see turbulence thus leads us to conclude that it must be driven by some physical stirring mechanism. In general, potential driving mechanisms include supernova explosions and expanding radiation fronts and shells induced by high-mass stellar feedback (McKee 1989;Balsara et al 2004;Krumholz et al 2006;Breitschwerdt et al 2009;Goldbaum et al 2011;Peters et al 2011;Lee et al 2012), winds , gravitational collapse and accretion of material (Vazquez-Semadeni et al 1998;Elmegreen & Burkert 2010;Klessen & Hennebelle 2010;Vázquez-Semadeni et al 2010;Federrath et al 2011b;Robertson & Goldreich 2012;Lee et al 2015), and Galactic spiral-arm compressions of H I clouds turning them into molecular clouds (Dobbs & Bonnell 2008;, as well as magnetorotational instability (MRI) and shear (Piontek & Ostriker 2007;Tamburro et al 2009). Jets and outflows from young stars and their accretion disks have also been suggested to drive turbulence (Norman & Silk 1980;Matzner & McKee 2000;Banerjee et al 2007;Nakamura & Li 2008;Cunningham et al 2009Cunningham et al , 2011Carroll et al 2010;Wang et al 2010;Plunkett et al 2013Plunkett et al , 2015Federrath et al 2014;Offner & Arce 2014).…”
Section: Turbulence Driving?mentioning
confidence: 99%
“…An initial trans-to supersonic turbulent velocity field as well as the subsequent injection of turbulence by accretion (Klessen & Hennebelle 2010;Arzoumanian et al 2013;Heitsch 2013) are not sufficient to stabilize a filament at a width of 0.1 pc. To overcome this problem, turbulence would have to be replenished in a more efficient way, e.g.…”
Section: Accretion Induced Turbulencementioning
confidence: 98%
“…As stated in Klessen & Hennebelle (2010), only a small fraction of the infalling energy can be converted into turbulent motions. Hence, in order to find out which amount of turbulence can be sustained by the observed infall rate, we have to solve the following equation for σ:…”
Section: Accretion Induced Turbulencementioning
confidence: 99%
“…High resolution threedimensional simulations of molecular clouds have shown that the star formation rate and efficiency depend on whether the turbulence is solenoidally or compressively driven (Federrath & Klessen 2012, and that the stellar initial mass function is sensitive both to non-ideal MHD effects such as ambipolar diffusion (McKee et al 2010) and to the driving and Mach number of the turbulence (Hennebelle & Chabrier 2009Hopkins 2013). The importance of stellar feedback (Krumholz et al 2007;Cunningham et al 2011;Myers et al 2014;Nakamura & Li 2007;Wang et al 2010; Price & E-mail: andrew.lehmann@mq.edu.au Bate 2008Bate , 2009Offner & Arce 2014;Federrath et al 2014;Federrath 2015;Padoan et al 2015), whether gravity drives turbulent motions (Elmegreen & Burkert 2010;Klessen & Hennebelle 2010;Vzquez-Semadeni et al 2010;Federrath et al 2011;Robertson & Goldreich 2012) and the role that turbulence plays in producing the ubiquitously observed filaments (Arzoumanian et al 2011;André et al 2014;Smith et al 2014Smith et al , 2016Federrath 2016;Kainulainen et al 2016;Hacar et al 2016) are big questions that continue to be studied. Rigorous observational effects distinctly revealing the presence or dominance of the various physical processes are strongly sought after.…”
Section: Introductionmentioning
confidence: 99%